The Future of Underwater Technology: Challenges and Opportunities for Indonesia in the Global Ocean Economy (Riset Sains dan Teknologi Kelautan, 2026)
A large-diameter single pile is a potentially attractive alternative for simplifying the foundation system of compact offshore jackets; however, concentrating all actions into one load path requires more rigorous geotechnical, structural, fabrication, and installation verification. This paper develops an integrated pre-design framework for assessing the concept. The assessment combines offshore structural design principles, soil–pile load-transfer mechanisms, axial and lateral capacity screening, tubular section stress checks, and fabrication quality planning. An illustrative reference case with a 3.0 m diameter steel pile, 60–80 mm wall thickness, 70 m total length, and 45 m embedment is used to demonstrate the influence of diameter, penetration, soil stiffness, wall thickness, and scour. The screening results indicate that axial resistance increases strongly with diameter and embedment, whereas lateral response is particularly sensitive to soil stiffness, diameter, and scour. For an illustrative combination of 20 MN axial load and 120 MN·m overturning moment, a 60 mm wall gives a combined nominal stress of approximately 337 MPa, leaving limited margin to a 355 MPa yield strength; increasing the wall to 70–80 mm reduces the stress to approximately 291–257 MPa. Fabrication reliability is governed by material traceability, ovality, alignment, welding parameters, non-destructive testing, corrosion protection, and loadout readiness. The concept can be efficient for light-to-medium topsides in relatively uniform ground, but it should not be selected merely because it reduces the number of piles. A final decision requires site-specific ground investigation, nonlinear soil–structure analysis, fatigue verification, drivability assessment, accidental limit-state checks, and installation-spread evaluation.